Osteoarthritis, COVID-19 Social Isolation-Impacts, and Counter Solutions - Marks Ray (Journal of Aging Research And Healthcare, 2020)
Background to the Issue Many older adults, including those already suffering from chronically painful disabling osteoarthritis of one or more joints remain more susceptible than healthy age and gender matched adults to the COVID-19 corona virus. Aims This report sought to examine what has been published in 2020 on this health condition from the perspective of the variable of widely imposed social isolation strategies designed to mitigate the spread of this highly infectious disease, and to especially keep older community dwelling adults ‘safe’ from infection. Methods Reviewed were all articles published in 2020 in PUBMED from January 1-December 24, 2020 on osteoarthritis and COVID-19 isolation impacts, plus relevant past osteoarthritis and isolation literature among older adults. The focus was on ascertaining how social isolation and distancing strategies might impact current community-dwelling adults diagnosed with osteoarthritis and whether more should be done specifically to mitigate any potentially preventable ‘socially’ induced negative health impact among this group, in spite of the laudable goals of this public health strategy. Results Older adults with osteoarthritis living in the community who are asked to self-isolate, may incur more osteoarthritis pain and disability than would otherwise be encountered if actions taken to counter this possibility are not forthcoming. Advocated over and above basic care approaches are several psychosocial strategies including the role of mobilizing various forms of social support. Conclusion Data indicate a need for concerted thoughtful and immediate attention to offset isolation, fear, and anxiety and depression effects as part of a carefully devised integrated plan of management to reduce excess osteoarthritis disability, as well as excess COVID-19 risk among otherwise free living older adults already compromised by osteoarthritis.
Keywords: Corona virus